Inscenizacja przemocy w pornografii a zakres kryminalizacji art. 202 § 3 k.k. - Nałęcz, Bartłomiej (PRAWO i WIĘŹ, 2025)
The paper addresses the issue of criminalizing the distribution of pornography containing violent motifs in light of Article 202 § 3 of the Criminal Code. The discussion covers staged content in which participants voluntarily take part in its creation. It discusses the definitional and cultural difficulties in determining the boundaries of pornography. At the same time, it presents arguments to justify the differentiation, for the purposes of criminal law, between real violence and its controlled expression through artistic or sexual means. An interpretative narrowing of the scope of criminalization under Article 202 § 3 of the Criminal Code was also proposed. According to this interpretation, in order to leave the dissemination of staged content outside this scope, it is necessary that: (1) the violence is simulated or controlled by the participants, (2) the participants give their conscious, voluntary consent to participate, and (3) the content is directed at a closed and informed audience. This distinction between criminalised and permissible pornography aims to protect dignity and respect individuals' right to self-determination in the sexual sphere.